PENGEMBANGAN WEBSITE TRACER STUDY DALAM MENINGKATKAN MUTU PROFIL LULUSAN - Sakina, Sakina; Thahir, Abdullah (Idaarah: Jurnal Manajemen Pendidikan, 2025)
This study aims to develop a valid, practical, and effective tracer study website at SMK Negeri 3 Barru to support the improvement of the quality of graduate profiles. This study uses the Research and Development (R&D) method with the ADDIE development model approach which includes five stages: analysis, design, development, implementation, and evaluation. Validation is carried out by material experts and media experts, while practicality and effectiveness are tested through questionnaires to the tracer study management team, tracer study admin, and alumni. Data collection techniques include interviews, observations, and questionnaires, with quantitative descriptive and qualitative data analysis. The results of the study showed that the tracer study website was in the valid category (92.3%), very practical according to the management team (84.5%), practical according to alumni (80.6%), effective according to admin (86%), and effective according to alumni (80.4%). These findings indicate that the developed tracer study website is worthy of being used to contribute to improving the effectiveness of tracer study reporting. In addition to facilitating alumni tracking, this website also provides strategic benefits through additional features such as job vacancies, digital alumni forms, and graduate profile information that can support active alumni participation and facilitate decision-making in improving the quality of vocational education, especially at SMKN 3 Barru.